Between Black and White: Analysis of Meaning Instability in the Film Maleficent - Ellin, Ellin; Hikmat, Mahi M (Universitas Airlangga, 2025)
This study examines the instability of meaning in the film Maleficent by deconstructing the conventional binary between good and evil commonly found in classic fairy tales. Rather than reinforcing moral absolutes, Maleficent challenges them by presenting a complex protagonist whose identity evolves from victim to villain to redeemer. Using Jacques Derrida’s theory of deconstruction and a qualitative-descriptive method, this research analyzes how narrative structure, symbolism, and character development disrupt fixed moral categories. The findings reveal that the film does not simply invert traditional roles but destabilizes the very foundations of moral storytelling. Meaning is portrayed as fluid, relational, and continuously shifting, emphasizing that identity and ethics in popular narratives are not fixed but open to reinterpretation.